The European Universities Initiative: Championing Excellence and Inclusion? - Rensimer, Lee; Brooks, Rachel (International Higher Education, 2023)
The European Universities Initiative is the European Commission’s ambitious strategy to integrate universities across the region into transnational alliances centering on common organizational, thematic, or challenge-focused missions. Over consecutive rounds beginning in 2019, the now 44 selected alliances are forming deep institutional partnerships, supported through an uneven patchwork of funding from the Commission, national governments, and institutions themselves, which appears to intensify inequalities in the European higher education landscape, pitting aims of excellence against inclusion.